Memory, belief and time. Issue 5 (December 2015) - Weatherson, Brian
Abstract: I argue that what evidence an agent has does not supervene on how she currently is. Agents do not always have to infer what the past was like from how things currently seem; sometimes the facts about the past are retained pieces of evidence that can be the start of reasoning. The main argument is a variant on Frank Arntzenius's Shangri La example, an example that is often used to motivate the thought that evidence does supervene on current features.